Tinjauan Pustaka: Faktor-Faktor Penyebab Rendahnya Penggunaan Metode Kontrasepsi Jangka Panjang (MKJP) - Adinda Fitriyani; Emi Sutrisminah (Jurnal MID-Z (MIDWIFERI ZIGOT), 2026)
The low use of MKJP contraceptives is caused by the wrong beliefs of some people regarding birth control, the lack of public awareness about the benefits of birth control and participants ignorance about the advantages of long-term contraceptive methods. The purpose of this study is to determine the factors causing the low use of MKJP. This literature review analysed 12 articles (2020–2025) from PubMed and Google Scholar to identify factors contributing to low MKJP utilization. The findings indicate that parity, knowledge, education, healthcare provider support, and spousal support influence MKJP use, with knowledge and partner support being the most significant factors. In conclusion, both individual and social factors affect MKJP utilization, highlighting the need for improved education and greater partner involvement in contraceptive decision-making in order to increase the use of MKJP.